The Hidden Burden of Trichinellosis in Vietnam: A Postoutbreak Epidemiological Study. (7th November 2013) - Vu Thi, Nga; Trung, Dung Do; Litzroth, Amber; Praet, Nicolas; Nguyen Thu, Huong; Nguyen Thu, Hien; Nguyen Manh, Hung; Dorny, Pierre
Abstract : A cross-sectional study was conducted in Muong Lat town (Thanh Hoa province, North Vietnam), following the confirmed diagnosis of trichinellosis in six patients from that town who had eaten hunted wild boar meat during the Vietnamese lunar year celebration. All inhabitants who declared to have eaten undercooked or raw wild boar meat at the celebration and showed at least one clinical symptom compatible with trichinellosis were included in the study and blood sampled. Anti- Trichinella IgG were determined by ELISA and Western Blot. Seropositive persons were given appropriate albendazole treatment and were followed up. A total of 100 inhabitants met the inclusion criteria. Among these, 30 (30%) had antibodies to Trichinella . Serologically confirmed cases had fever (90.0%), myalgia (86.7%), facial oedema (63.3%), diarrhoea (53.3%), and pain of the masseter muscles (43.3%). Eosinophilia was detected in 83.3% of these individuals. Clinical symptoms resolved in all patients during albendazole treatment. The results suggest that only a proportion of the trichinellosis cases had sought health care during the outbreak. There is a need to implement surveillance and better diagnosis for trichinellosis and to set up educational programs to prevent infection in North Vietnam.